2001
DOI: 10.1128/aem.67.7.3236-3244.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Small Tetraheme Cytochrome c and a Flavocytochrome c as Two of the Principal Soluble Cytochromes c in Shewanella oneidensis Strain MR1

Abstract: Two abundant, low-redox-potential cytochromesc were purified from the facultative anaerobeShewanella oneidensis strain MR1 grown anaerobically with fumarate. The small cytochrome was completely sequenced, and the genes coding for both proteins were cloned and sequenced. The small cytochrome c contains 91 residues and four heme binding sites. It is most similar to the cytochromes c fromShewanella frigidimarina (formerly Shewanella putrefaciens) NCIMB400 and the unclassified bacterial strain H1R (64 and 55% iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…Similar bands (417-418, 521-522 and 551 nm) were also found in dithionite-reduced periplasmic proteins from cells grown on nitrate and O 2 (air) ( Table 1). The absorption maxima at 417-419, 522 and 551 nm corresponded, respectively, to the c (Soret), b and a bands of c-type cytochrome in the reduced state (Poole, 1994), and are similar to those of ctype cytochromes found in other strains of Shewanella (Tsapin et al, 2001;Pitts et al, 2003;Yamada et al, 2000). Freshly prepared or air-oxidized periplasmic proteins from nitrate-or O 2 (air)-grown cells showed a single maximal band at 410 or 413 nm, corresponding to the c band of oxidized c-type cytochrome.…”
Section: In Vitro Anaerobic Rdx Metabolism By Periplasmic Proteinsmentioning
confidence: 57%
See 1 more Smart Citation
“…Similar bands (417-418, 521-522 and 551 nm) were also found in dithionite-reduced periplasmic proteins from cells grown on nitrate and O 2 (air) ( Table 1). The absorption maxima at 417-419, 522 and 551 nm corresponded, respectively, to the c (Soret), b and a bands of c-type cytochrome in the reduced state (Poole, 1994), and are similar to those of ctype cytochromes found in other strains of Shewanella (Tsapin et al, 2001;Pitts et al, 2003;Yamada et al, 2000). Freshly prepared or air-oxidized periplasmic proteins from nitrate-or O 2 (air)-grown cells showed a single maximal band at 410 or 413 nm, corresponding to the c band of oxidized c-type cytochrome.…”
Section: In Vitro Anaerobic Rdx Metabolism By Periplasmic Proteinsmentioning
confidence: 57%
“…Regulation by TEA of c-type cytochrome production in S. halifaxensis Several strains of Shewanella have been reported to produce c-type cytochromes capable of reducing insoluble metal oxide (Tsapin et al, 1996(Tsapin et al, , 2001Gordon et al, 2000). In the present study, the cytochrome content of S. halifaxensis HAW-EB4 grown under both anaerobic and aerobic conditions was characterized and determined for its potential involvement in RDX metabolism.…”
Section: In Vitro Anaerobic Rdx Metabolism By Periplasmic Proteinsmentioning
confidence: 99%
“…These proteins include CymA, a tetraheme c-type cytochrome anchored to the inner membrane that serves as a MQH 2 dehydrogenase [8,12,20,43,44]; Stc, a 12-kDa tetraheme periplasmic c-type cytochrome [15,45] and the periplasmic decaheme cytochrome MtrA [10] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Electron transport proteins proposed to be involved in Fe(III) respiration in Shewanella oneidensis MR-1 include an inner-membrane periplasmic tetraheme quinol dehydrogenase (CymA) [8,12], two periplasmic decaheme cytochromes (MtrD and MtrA) [10,13], periplasmic tetraheme cytochrome (Stc) [14,15], the cytochrome domain of Fe(III)-induced flavocytochrome c 3 , [16] two putative outer-membrane b-barrel proteins (MtrE and MtrB) [17][18][19] and three outer-membrane decaheme cytochromes (MtrF, OmcA and MtrC) [11,18,20,21]. Although genetic studies have identified specific proteins that are involved in Fe(III) respiration in Shewanella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is not known which of these cytochromes are necessary to bridge the periplasmic gap between CymA and the outer membrane. Interestingly, the fumarate reductase FccA and the small tetraheme cytochrome (STC) (CctA) are highly abundant in the periplasm under anoxic conditions (Tsapin et al, 2001;Meyer et al, 2004). Nevertheless, although it was suggested that they might have a role in the transfer of electrons to the outer membrane, a corresponding phenotype under conditions of ferric iron or dimethyl sulfoxide (DMSO) reduction was not shown so far (Gordon et al, 2000;Schuetz et al, 2009;Fonseca et al, 2013).…”
Section: Introductionmentioning
confidence: 99%